Strategic Initiatives of The Batik Women’s Association (Iwatik) Balikpapan - Nilawati, Nilawati; Sukadi, Iwan Sariono; Bessy, Dian Savira; ZA, Saida Zainurossalamia (Green Publisher Indonesia, 2026)
Micro, Small, and Medium Enterprises (MSMEs) have a vital role in the Indonesian economy, but their sustainability is highly dependent on the implementation of effective management strategies. This article analyzes the strategic and business management practices of Iwatik Batik Balikpapan MSMEs, a group fostered by the Balikpapan City Cooperatives, MSMEs, and Industry Office established by Sri Sunarti since 2015. Using a qualitative descriptive analysis approach, this article examines how Iwatik applies differentiation strategies through typical Kalimantan batik motifs such as squid arches, karamunting fruits, marsh bags, tiwai onions, and mangroves. The SWOT analysis identified Iwatik's competitive advantage in the quality of hand-painted batik and the uniqueness of local motifs, as well as great opportunities from the momentum of moving the National Capital City (IKN) of the archipelago to East Kalimantan. The results of the analysis show that Iwatik's success lies in the implementation of product differentiation strategies, market development, sustainable innovation, and the integration of the social mission of women's empowerment with cultural preservation. Iwatik also leverages digital marketing and strategic partnerships with governments and corporations to expand its market reach. These findings provide an important lesson for other MSMEs that differentiation based on local excellence, sensitivity to external opportunities, strong branding, and commitment to quality are the keys to sustainability and business growth. This article concludes that with the right strategic management, culture-based MSMEs like Iwatik can compete in a competitive market while preserving cultural heritage and having a positive socio-economic impact on society.